Improving the bonding between henequen fibers and high density polyethylene using atmospheric pressure ethylene-plasma treatments - A. Aguilar-Rios; P. J. Herrera-Franco; A. de J. Martinez-Gomez; A. Valadez-Gonzalez (eXPRESS Polymer Letters)
In order to improve the bonding between henequen fibers (Agave fourcroydes) and High Density Polyethylene (HDPE), they were treated in an ethylene-dielectric barrier discharge (DBD) plasma operating at atmospheric pressure. A 23 factorial experimental design was used to study the effects of the plasma operational parameters, namely, frequency, flow rate and exposure time, over the fiber tensile mechanical properties and its adhesion to HDPE. The fiber-matrix Interfacial Shear Strength (IFSS) was evaluated by means of the single fiber pull-out test. The fiber surface chemical changes were assessed by photoacoustic Fourier transform infrared spectroscopy (PAS-FTIR) and the changes in surface morphology with scanning electron microscopy (SEM). The results indicate that individual operational parameters in the DBD plasma treatment have different effects on the tensile properties of the henequen fibers and on its bonding to HDPE. The SEM results show that the plasma treatment increased the roughness of the fiber surface. The FTIR result seems to indicate the presence of a hydrocarbon-like polymer film, bearing some vinyl groups deposited onto the fibers. These suggests that the improvement in the henequen-HDPE bonding could be the result of the enhancement of the mechanical interlocking, due the increment in roughness, and the possible reaction of the vinyl groups on the film deposited onto the fiber with the HDPE.